Penerapan Animasi 3D Pada Saat Melakukan Gerakan Wourkout Menggunakan Metode Pose To Pose - Prayuda, Angga; Khairani, Sumi; Dharmawati, Dharmawati (Universitas Harapan Medan, 2023)
Workout is an activity that someone does to improve or maintain body fitness. Workout does require moving the body with good concentration and coordination so that the results are maximized, if you lose your focus even a little during your workout, the consequences can range from minor to serious injuries. One way to overcome this problem is to take advantage of the existing information and communication technology, namely by making the stages of the process of how to move properly and correctly with an animated display. The purpose of this animated video is to provide direction and an overview of how to make it easier by following the stages simulated in 3D animation. This study discusses one of the methods related to the basic principles of animation, namely the pose to pose method. The discussion of the method is carried out by applying 3D animation when doing workout movements using 3D figure objects to demonstrate the workout movements. The design of the animation in this study was carried out through three stages, namely pre-production, production and post-production using the Blender application. This research succeeded in implementing human movement during workouts in the form of 3D animation.